Penerapan Media Story Puzzle dalam Meningkatkan Literasi Belajar Peserta Didik pada Mata Pelajaran IPS - Fazriyani, Felinda; Wahyudi, Deny Yudo; Sumariyani, Sumariyani (Program Studi Tadris IPS Fakultas tarbiyah IAIN Kudus, 2025)
The low interest in reading of students affects their understanding of complex social studies material. This study aims to describe the planning, implementation, and evaluation of the use of Story Puzzle media to improve students' learning literacy in social studies subjects. The research method uses a descriptive qualitative approach, with data collection techniques in the form of participatory observation, semi-structured interviews, and documentation. The subjects of the study included social studies teachers and class VII F students of SMP Negeri 19 Malang. Data analysis used the interactive model of Miles, Huberman, and Saldana. The results of the study showed that the planning of Story Puzzle media was carried out through analysis of student needs and development of teaching modules. Implementation refers to the Teams Games Tournament model through five stages: information delivery, team formation, games, matches, and team recognition. The evaluation showed that Story Puzzle media was effective in improving the ability to understand text, interpret information, analyze, evaluate, and communicate understanding. This media creates fun, collaborative, and contextual learning in accordance with 21st century learning and develops critical thinking skills, communication, collaboration, and creativity.